Investigating the physical activity demographic profile of student-teachers at an open distance learning institution, Kuala Lumpur - Mahmood, Rosinah; Hassan, Roshafiza; Loo, Fung Lan; Ismail, Md Rosli (Secholian Publication, 2024)
Physical activity (PA) is crucial for maintaining a healthy lifestyle, yet it is often overlooked, and many individuals do not engage in regular exercise. In recent years, the rise of Open Distance Learning (ODL) institutions has transformed the educational landscape, enabling students to learn from various locations, including the convenience of their homes. However, this shift to distance learning may contribute to a sedentary lifestyle, particularly for student-teachers who spend extended hours in front of computer screens. This study investigates the health demographic profile of student-teachers within an Open Distance Learning (ODL) institution, emphasizing the impact of distance learning on physical activity levels. With 206 participants, a self-developed questionnaire was used for data collection. Findings revealed a generally low level of physical activity among student-teachers, highlighting the need for increased time, motivation, and suitable facilities. The study underscores the potential long-term consequences of poor health status and limited engagement in physical activities. Recommendations include encouraging student-teachers to incorporate even low-intensity movements into their daily routines. The implications and recommendations are discussed to address the sedentary lifestyle, emphasizing the importance of promoting physical activity for overall well-being.